Geospatial Modeling of Soil Plasticity Index and Water Content Distribution in Coastal Bengkulu: A Basis for Resilient Infrastructure Planning - Putri, Melly Zuhadjar; Mase, Lindung Zalbuin; Amri, Khairul; Misliniyati, Rena; Hardiansyah, Hardiansyah; Refrizon, Refrizon (Journal Innovation of Civil Engineering (JICE), 2025)
Bengkulu Province, located along the western coast of Sumatra, is one of Indonesia’s most seismically vulnerable regions due to its proximity to major tectonic boundaries. This study aims to enhance earthquake-resilient infrastructure planning by developing a two-dimensional geospatial model of key geotechnical parameters—Plasticity Index (PI) and water content (ѡ) —in the coastal zone. A total of 65 geotechnical observation points served to generate detailed maps by using the Inverse Distance Weighting (IDW) method down to 30 meters depth. The model integrates empirical correlations with statistical and spatial analyses to overcome the challenges of limited data. Results highlight distinct geotechnical variations across different soil layers and administrative regions, revealing zones with high liquefaction potential. The findings provide insight for engineers, urban planners, and disaster risk authorities in designing site-specific construction strategies. This research fills a critical gap in the current literature regarding Inverse Distance Weighting (IDW)-based geospatial modelling in seismically active areas. It offers a replicable framework for other coastal regions with similar geological contexts. Keywords: Plasticity Index; Water Content; Geospatial modeling; Inverse Distance Weighting (IDW)